Accumulative weekly load in a professional football team: with special reference to match playing time and game position - Casamichana, D.; Martín-García, A.; Gómez Díaz, A.; Bradley, S. P.; Castellano, J. (Biology of Sport, 2022)
The aim of this study was to compare weekly accumulative load during the in-season competitive period by professional soccer players according to the amount of time played in official matches (90-min, >60-min, <60-min, and 0-min) regarding the players` position. Twenty-four professional outfield football players were monitored by GPS devices during training sessions and official matches and the accumulative weekly load were calculated for the following external load variables: total distance (TD; m), high speed running (HSR; >19.8 km·h-1), sprint meters (SPR; >25.2 km·h-1), high metabolic load distance (HMLD; >25.5 W·kg-1), number of accelerations (ACC; >3 m·s-2) and decelerations (DEC; <-3 m·s-2). This study revealed that players (as a whole o per demarcation) with more match playing time had a higher accumulative weekly load for most of the variables, but particularly at TD and HMLD (90-min and >60-min vs. <60-min and 0-min), HSR (90-min vs. <60-min and 0-min) and SPR (90-min vs. <60-min and 0-min). In addition, less positional variation was observed in relation to the competition requirements. This information would allow coaches to refine the required load with the objective of optimizing performance to soccer players.